Expression and purification of ShLysG in Escherichia coli and initial characterization of its antimicrobial, antioxidant and anti-inflammatory activities. (December 2020) - Dong, Bin; Sun, Chunlong; Wu, Tao; Wang, Jun; Wang, Baogui; Du, Wen
Graphical abstract: Highlights: The rShlysG exhibited a broad antimicrobial spectrum. The rShlysG showed low hemolytic activity and no cytotoxicity. The rShlysG was thermostable and insensitive to pHs. The rShlysG showed strong antioxidant activity. The rShlysG decreased the expression of inflammatory cytokines. Abstract: ShLysG is a novel g-type lysozyme isolated from Hippocampus abdominalis in 2016. However, its antibacterial, antioxidant and anti-inflammatory properties have not been investigated. In this study, a recombinant ShLysG (rShLysG) fused with a 6×His tag was produced in Escherichia coli with barely any hemolytic activity or cytotoxicity. It exhibited a broad antimicrobial spectrum against gram-positive and gram-negative bacteria with minimum inhibitory concentration (MIC) values between 20 and 60 μg/mL. The bioactivity of rShLysG was stable in high temperature and extreme acid base conditions. In addition, rShLysG was resistant to papain and pepsin, and it showed a concentration-dependent antioxidant activity. By inhibiting the phosphorylation of NF-κB, the inflammatory cytokines expression level, including TNF-α, IL-6, and IL-8 in RAW264.7 macrophage cells induced by LPS were decreased. Taken together, rShLysG is a promising substitute to antibiotics as an antimicrobial and immunoregulatory pharmaceutical peptide for clinical use.